Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from Celebrity Equinox in the Adriatic Sea, Aegean Sea and others from 2015-02-23 to 2016-01-02 (NCEI Accession 0157224) ... - Wanninkhof, Rik; Pierrot, Denis; Huss, Betty E.; Sullivan, Kevin F.; Castle, Robert D. (NOAA National Centers for Environmental Information, 2016)
This dataset includes Surface underway, chemical, meteorological and physical data collected from Celebrity Equinox in the Adriatic Sea, Aegean Sea, Alboran Sea, Balearic (or Iberian) Sea, Caribbean Sea, Coastal Waters of Florida, Gulf of Mexico, Ionian Sea, Ligurian Sea, Mediterranean Sea, Mediterranean Sea - Eastern Basin, Mediterranean Sea - Western Basin, North Atlantic Ocean, Sea of Marmara, Strait of Gibraltar and Tyrrhenian Sea from 2015-02-23 to 2016-01-02. These data include AIR-SEA DIFFERENCE - PARTIAL PRESSURE (OR FUGACITY) OF CARBON DIOXIDE, BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - atmosphere, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY and SEA SURFACE TEMPERATURE. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and thermosalinographs. These data were collected by Denis Pierrot, Kevin F. Sullivan, and Rik Wanninkhof of NOAA ...